Metacognitive approach based on differences in self-regulated learning skills toward mathematical reflective thinking for primary school students - Cahyani, Nafisa Fitri; Amir, Mohammad Faizal; Wardana, Mahardika Darmawan Kusuma (Universitas Islam Negeri Raden Intan Lampung, 2025)
Mathematical reflective thinking, a cornerstone of deep comprehension and effective problem-solving, frequently presents student challenges. This research explores the efficacy of a metacognitive strategy, examining its influence on primary school students' mathematical reflective thinking, particularly considering variations in Self-Regulated Learning (SRL) abilities. This research employed the quantitative methodology with a quasi-experimental design, incorporating pre-test and post-tests with non-randomized groups. Fifty fifth-grade students participated, and data was gathered through assessments and questionnaires. Statistical analysis, including univariate tests and independent samples t-tests, was conducted. The findings revealed a significant impact, with a p-value of 0.040 and an R-squared value of 0.855, indicating that 85.5% of the variance in reflective thinking could be attributed to the metacognitive approach. Notably, students demonstrating higher SRL levels exhibited a greater propensity to enhance their reflective thinking through metacognitive processes, such as planning, monitoring, and evaluation. Consequently, future research should explore reflective thinking with diverse learning interventions while still considering SRL differences and focusing on strengthening SRL generalization activities. This study implied that a metacognitive approach is a valuable pedagogical tool for educators and researchers aiming to foster mathematical reflective thinking while acknowledging and addressing individual cognitive variations, especially those related to SRL.